1998
DOI: 10.1021/jp981101a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Gas-Phase Addition of the Ethyl Radical and the tert-Butyl Radical to NO

Abstract: The kinetics of the addition reaction of the ethyl radical and the tert-butyl radical to NO has been investigated at 1.5 bar as a function of temperature (219−475 K) using the muon spin relaxation technique in longitudinal magnetic fields. The data are represented by k 1 = ( ) × 10-10 T -0.5±0.1 cm3 molecule-1 s-1 for the ethyl radical and k 2 = ( ) × 10-4 T -3.1±0.2 cm3 molecule-1 s-1 for the tert-butyl radical, or alternatively by Arrhenius parameters of E a = −(1.4 ± 0.3) kJ mol-1 and A = (1.3 ± 0.2) × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…No rate constant could be found in the literature for the reaction of a bridgehead radical with NO but previous studies of reactions of carboncentred radicals with NO have been reported and represent an interesting comparison. The rate constant for the reaction of tertbutyl with NO determined by the muon spin relaxation technique is 1.0 ± 0.3 × 10 −11 cm 3 molecule −1 s −1 and that for ethyl radical is 2.2 ± 0.6 × 10 −11 cm 3 molecule −1 s −1 at 307 K. 38 A value of 3.5 ± 0.1 × 10 −11 cm 3 molecule −1 s −1 was measured by colour centre laser kinetic spectroscopy for the reaction of ethynyl radical with NO 39 and 9.5 ± 1.2 × 10 −12 cm 3 molecule −1 s −1 for benzyl radical with NO at 298 K by laser flash photolysis. 40 Our value compares favourably with these, with a rate constant ca.…”
Section: Methodsmentioning
confidence: 87%
“…No rate constant could be found in the literature for the reaction of a bridgehead radical with NO but previous studies of reactions of carboncentred radicals with NO have been reported and represent an interesting comparison. The rate constant for the reaction of tertbutyl with NO determined by the muon spin relaxation technique is 1.0 ± 0.3 × 10 −11 cm 3 molecule −1 s −1 and that for ethyl radical is 2.2 ± 0.6 × 10 −11 cm 3 molecule −1 s −1 at 307 K. 38 A value of 3.5 ± 0.1 × 10 −11 cm 3 molecule −1 s −1 was measured by colour centre laser kinetic spectroscopy for the reaction of ethynyl radical with NO 39 and 9.5 ± 1.2 × 10 −12 cm 3 molecule −1 s −1 for benzyl radical with NO at 298 K by laser flash photolysis. 40 Our value compares favourably with these, with a rate constant ca.…”
Section: Methodsmentioning
confidence: 87%
“…20 The reaction kinetics of tert-butyl have been studied in the condensed phase [21][22][23] and the gas phase. 11,[24][25][26][27][28][29][30] The unimolecular decay of tert-butyl is of particular relevance to this work as a reference point for ground state dissociation dynamics. Knyazev et al 26 determined the rate constant for thermal decomposition of tert-butyl from 712-779 K using photoionization mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies of this nature, muonium exhibits a primary KIE, but the Mu atom has also been used as a passive spectator in kinetic studies of radical reactions where the bond to Mu remained intact and where any secondary KIE was undetectable, within error. Such work includes the determination of accurate and absolute rate constants of radical clock reactions such as cyclization and ring fission in the liquid phase and of Mu−ethyl radical addition reactions to O 2 and NO. , …”
Section: Introductionmentioning
confidence: 99%